JURNAL KHOYAK - Duwi Novrianti (Saraswati)
This dance work is entitled Khoyak, which in Melayu language means ‘shaking’. This dance work reflects about the spirit to work together, to coordinate dan the dancers’ balance when they are making interaction with their lukah (s). This lukah gilo game is always started with a bomo or supranaturalist that moves the bamboo stick in his hand and sings a ‘mantera’ (spell) that makes the lukah which is held by peladen (s) moving anywhere the bamboo moved by the bomo. This dance work is also developing a motive in Zapin Dance that is meniti batang motive which has a similar pattern of movement with the lukahwhen it is spelled with the ‘mantera’. This dance work does not expose the ritual of the lukah gilo game, but it ismore showing the game or exploration with the ‘lukah’ as dance property. Lukah in the Khoyak dance work is done in unnecessarily ways which is always played in hands (of peladen), but it can be done with feet and to be bitten. This gamepresents a fun sitution from the five dancers’ spirits when they are playing with their lukah (s), and there is a part telling a story on an event (making lukah onpart 1 of the dance).